Parity and Marital Status as Factors Influencing Contraceptive Use among Adolescents in Indonesia - Mas'udah, Anni Fithriyatul; Pristya, Terry YR; Andarmoyo, Sulistyo (UI Scholars Hub, 2021)
Adolescent pregnancy has a higher health risk compared to adult pregnancy. One approach to control pregnancy among adolescents is through contraceptive use. The data on contraceptive use has increased in 2018 and is still controversial among adolescents. Thus, it is necessary to determine the factors encou - rag ing the use of contraceptives among adolescents. This study aimed to determine the relation of parity and marital status on contraceptive use among adolescents. This quantitative study used a cross-sectional design. The population of this study was adolescents aged 15–19 years in Indonesia. The total sample of 936 adolescents was selected from the 2017 Indonesia Demographic and Health Survey (IDHS). Multivariate analysis using binary logistic regression was used to analyze the independent variables (parity and marital status) on the dependent variable (contraceptive use) with education, work status, region, and economic status as controls. The results showed relationship association between marital status and parity on contraceptive use in adolescents after being controlled by confounding variables , namely work status, economic status and region. The use of contraceptives was one way to control adolescent pregnancy. Counseling and guidance concerning the use of contraceptives should be provided to adolescents.